ANALISIS PERUBAHAN CURAH HUJAN SATELIT TROPICAL MEASURING MISSION (TRMM) TAHUN 2009 DAN TAHUN 2010 - Zubaidah, Any (MAJALAH ILMIAH WIDYA, 2012)
The utilization of a combination of sensor data PR (Precipitation Radar) and TMI (TRMM Microwave Imager) satellite carriedby the TRMM (Tropical Rainfall Measuring Mission) can be used to analyze the characteristics and mechanisms of rainfall in tropicalregions. It was applied in the territory of Indonesia. The aim of this study was to analyze the rainfall of TRMM data in 2009 and 2010in order to understand each characteristic and phenomenon that occurs. TRMM data that were used was type of 3B43.. The researchmethod that applied included a search pattern of spatial and temporal rainfall obtained from the processing of TRMM rainfall data.The results showed that the rainfall data in 2009 and 2010 from TRMM satellite monitoring is able to represent the rainfall conditionsduring extreme conditions in the territory of Indonesia, either at the time of El NiÃ±o and La NiÃ±a. In 2009 occurred the phenomenonof El Nino, while the year 2010 was phenomenon of La Nina.